2018
DOI: 10.1186/s13287-018-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

Metformin induces apoptosis in mesenchymal stromal cells and dampens their therapeutic efficacy in infarcted myocardium

Abstract: BackgroundCardiovascular complications, especially myocardial infarctions (MIs), are the leading mortality cause in diabetic patients. The transplantation of stem cells into damaged hearts has had considerable success as a treatment for MI, although whether antidiabetic drugs affect the therapeutic efficacy of stem cell transplantation is still unknown. This study aims to understand whether and how metformin, one of the first-line drugs used to treat type 2 diabetes mellitus (T2DM), induces mesenchymal stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
(47 reference statements)
2
14
2
Order By: Relevance
“…However, the results are in contradiction to data presented by He et al [65], who showed that metformin significantly induces apoptosis of MSCs isolated from human umbilical cord, even at 0.1 mM concentration. He et al showed that metformin induces apoptosis in cells in dose- and time-dependent manner, and indicated that metformin at 2 mM concentration induced a sub-G1 peak, which is a suggestive marker of apoptosis [65]. We confirmed the anti-apoptotic activity of metformin in EqASC cultures at different levels.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results are in contradiction to data presented by He et al [65], who showed that metformin significantly induces apoptosis of MSCs isolated from human umbilical cord, even at 0.1 mM concentration. He et al showed that metformin induces apoptosis in cells in dose- and time-dependent manner, and indicated that metformin at 2 mM concentration induced a sub-G1 peak, which is a suggestive marker of apoptosis [65]. We confirmed the anti-apoptotic activity of metformin in EqASC cultures at different levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results clearly indicate that metformin improves EqASC viability. Additionally, we noted increased transcript levels of the anti-apoptotic BCL-2 gene, in contrast to the findings of He et al [65]. The discrepancy between our findings and those of He et al may be due to the model used, as well as different metformin concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies show decreased osteoclastogenesis in murine-derived preosteoclasts using supra-pharmacological concentrations of metformin [196,197,198]. However, some in vitro studies have shown MSC apoptosis following transplantation and decreased angiogenic potential of human MSCs treated with metformin [199,200]. In human-induced pluripotent MSCs, metformin enhanced osteoblastic activity by increasing ALP activity and mineralized nodule formation, which was partly mediated by the LKB1/AMPK pathway [201].…”
Section: Effects Of Insulin and Anti-diabetic Drugsmentioning
confidence: 99%
“…Recently, our group found a significant decrease in the abundance of circulating MSCs, which was correlated with complications in patients with T 2 DM 19 . In addition, we found the unexpected adverse effect that metformin, as a first-line agent used to treat T 2 DM and a basic glucose-lowering drug used during intensive glucose control, significantly induced MSC apoptosis and damped their therapeutic efficacy in infarcted myocardium 20 . However, the role of glucose during metformin-induced MSC apoptosis in diabetes remains unknown.…”
Section: Introductionmentioning
confidence: 94%